(untitled) (Proceedings of the World Conference on Women’s Studies, 2022)
The thin line between art and politics concerning women’s objectification is one of the most apparent problems in the representation of the female body in sex markets and creative spaces. This paper aims to explore and provide a philosophical analysis on women’s objectification and the male construction of female sexuality and femininity apparent in Nobuyoshi Araki’s controversial and sexually explicit photographs. To attain this, I derive from the ethical theory of Kant and his views on the “beautiful” embodied by women, and the moral problem presented by Nussbaum on the legalization of bodily services. I employ the carceral-neoliberalism approach through the method of philosophical analysis to problematize the treatment of women’s bodies under the sheets of high-value art, policy-making, and commodification. The curatorial and commentary of Araki’s photographs as case studies aim to juxtapose the ethical theories and the underlying problems of female sexuality. Therefore, the peculiarities in Araki’s works—presented as the female nude—are addressed and problematized. The discussions are divided in the following: (1) Kantian notions on the female, (2) Nussbaum’s theory on bodily services, (3) Carceral-neoliberalism approach to feminism, and (4) the case study on Araki’s sexually explicit photographs. The results of the discussion show that the portrayal of women in Araki’s photographs establishes the link between the female’s body and her sexuality. Assertions of objectification and personification are byproducts of the male gaze as well as a patriarchal indoctrination and colonization of women and their bodies. Repercussions of neoliberalism are also reflected in the marketization of women. I finally conclude that the necessity of continuously framing the problems in women’s sexuality should be recognized so stigmatization against women may be eradicated.